2000
DOI: 10.1007/s002510050622
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear factor-??B in the expression by tumor necrosis factor-? of the human polymeric immunoglobulin receptor ( pIgR ?) gene

Abstract: We analyzed the mechanism of human polymeric immunoglobulin receptor (pIgR) gene upregulation by tumor necrosis factor (TNF)-alpha. Northern blot analysis showed that the expression of pIgR mRNA was enhanced by TNF-alpha stimulation. This activation was completely inhibited by RNA polymerase or protein synthesis inhibitors, suggesting that the regulation of pIgR gene expression depends on de novo RNA and protein synthesis. Furthermore, the stimulation of pIgR mRNA by TNF-alpha was decreased by pyrrolidinedithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…The best-characterized mediator of TNF action is the NF-B family of latent, rapidly activated transcription factors (TFs) (11,12). Up-regulation of pIgR mRNA by TNF is sensitive to NF-B inhibitors (13). We have recently demonstrated that TNF-mediated up-regulation of pIgR in the human intestinal adenocarcinoma cell line HT-29.m3 required cooperation between DNA elements located in both an enhancer region of intron 1 and the proximal promoter (14).…”
Section: And 7)mentioning
confidence: 99%
See 2 more Smart Citations
“…The best-characterized mediator of TNF action is the NF-B family of latent, rapidly activated transcription factors (TFs) (11,12). Up-regulation of pIgR mRNA by TNF is sensitive to NF-B inhibitors (13). We have recently demonstrated that TNF-mediated up-regulation of pIgR in the human intestinal adenocarcinoma cell line HT-29.m3 required cooperation between DNA elements located in both an enhancer region of intron 1 and the proximal promoter (14).…”
Section: And 7)mentioning
confidence: 99%
“…The role of RelB as an activator of pIgR transcription differentiates the regulation of this gene with that of classical proinflammatory genes expressed upon TNF stimulation of epithelial cells such as IL-8 (35). However, activation of p65/ p50 is presumably also critical for pIgR activation because it is required for activation of the RelB gene itself (13,31). It is tempting to speculate that this dimer also binds to target elements in the pIgR gene at early time points after TNF stimulation and is exchanged for RelB-containing dimers at a later time point to achieve a sustained activation.…”
Section: Possible Involvement Of Different Nf-b Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the role of two previously reported putative TNF-␣-responsive elements: an ISRE in exon 1 (26,27) and an NF-B/Rel site centered around position Ϫ450 in the upstream promoter (18,25). The former is 100% conserved between human, rat, and murine sequence, although the position relative to the transcriptional start site differs somewhat (Fig.…”
Section: An Isre In Exon 1 Is Required For Full Tnf-␣ Responsiveness mentioning
confidence: 99%
“…3 and 24). TNF-␣-mediated transcriptional up-regulation of pIgR/SC was shown to depend on NF-B/Rel activation (25) and an IFN-stimulated response element (ISRE) located in exon 1 (26,27). However, the effect mediated by described DNA elements could not account for the degree of up-regulation indicated by the increased level of mRNA and by nuclear run-on experiments (18).…”
mentioning
confidence: 99%